Rutaecarpine Protects against Acetaminophen-Induced Acute Liver Injury in Mice by Activating Antioxidant Enzymes - Jae Ho Choi; Sun Woo Jin; Gi Ho Lee; Eun Hee Han; Yong Pil Hwang; Hye Gwang Jeong (MDPI AG, 2021)
Rutaecarpine, an indolopyridoquinazolinone alkaloid isolated from the unripe fruit of Evodia rutaecarpa, is used to treat hypertension, postpartum hemorrhage, dysentery, and amenorrhea as a traditional medicine in Asia. We investigated the effect of rutaecarpine on acetaminophen-induced hepatotoxicity in mice. Rutaecarpine was administered orally daily for seven consecutive days, followed by intraperitoneal injection of acetaminophen in mice on day seven to induce hepatotoxicity. Rutaecarpine pretreatment significantly decreased acetaminophen-induced serum alanine aminotransferase (ALT)/aspartate aminotransferase (AST) activities and hepatic malondialdehyde content and prevented acetaminophen-induced hepatic glutathione depletion. Furthermore, CYP2E1 expression was decreased by rutaecarpine pretreatment in a dose-dependent manner. Rutaecarpine pretreatment inhibited acetaminophen-induced expression of inflammatory cytokines by inhibiting NF-κB activation by JNK1/2. Also, rutaecarpine pretreatment promoted Nrf2-mediated activation of the antioxidant enzymes GCLC, HO-1, and NQO1. This indicates that the protective effect of rutaecarpine during acetaminophen-induced acute liver injury is mediated by the activation of antioxidant enzymes. Therefore, rutaecarpine has a protective effect of APAP-induced liver damage.